Contribuição tônica do quimiorreflexo carotídeo para o controle vagal cardíaco no repouso, ortostatismo e durante a recuperação após o exercício em pacientes com hipertensão arterial pulmonar - Ribeiro, Marcelle de Paula [UNIFESP] (2018)
Pulmonary Arterial Hypertension (PAH) is a rapidly progressive disease with multiple etiologies and an extremely poor prognosis. Patients with PAH present marked autonomic dysfunction, characterized by increase in sympathetic activity and reduction in vagal activity to cardiovascular system. The augmented peripheral chemoreflex responsiveness seems to play a role on autonomic dysfunction in PAH. However, remains unclear the tonic contribution of the peripheral chemoreflex to cardiac vagal control in PAH. We hypothesized that the carotid chemoreflex would impair the cardiac vagal control at rest and during orthostatic challenge in patients with PAH and this impairment would be increased during post-exercise recovery, since evidences have shown that the peripheral chemoreflex might be sensitized by different substances released during exercise. To test these hypothesis, 20 patients with established PAH and 13 age and sex matched healthy controls (CON) took part of the study. Both groups underwent to peripheral chemoreflex sensitivity evaluation through transient hypoxic inhalation. Afterwards, they were randomly exposed to 1) hyperoxia (carotid chemoreflex inhibition, 100% O2), or 2) normoxia (control session, 21% O2); during cardiac vagal modulation assessment (baroreflex sensitivity [BRS]; heart rate variability [HRV]; heart rate recovery [HRR]). Data are shown as mean ± SD and comparisons between gases and groups were acquired using the Mixed Linear Model (p ≤ 0.05). The PAH showed peripheral chemoreflex sensitivity to hypoxia compared to CON (P=0.01). During rest, hyperoxia increased vagal indexes of HRV and BRS in both PAH and CON groups, and this increase was similar among groups, indicating that the carotid chemoreflex tonically modulates the cardiac vagal control in healthy subjects and patients with PAH. During orthostatic challenge, hyperoxia increased BRS in both groups and this effect was greater in PAH, indicating that the carotid chemoreflex is sensitized in PAH and contributes to impaired BRS during orthostatic challenge in this group. During post-exercise recovery, hyperoxia increased HRR and HRV in both groups and this effect was greater in PAH, indicating that the carotid chemoreflex is sensitized in PAH and contributes to impaired post-exercise vagal reactivation in this group. Taking together, the results suggest that the carotid chemoreflex tonically modulate the cardiac vagal control in healthy humans and contributes to cardiac vagal dysfunction during orthostatism and during post-exercise recovery in patients with PAH.